Maternal Diabetes and Intra-Familial Marriage as Risk Factors for Congenital Heart Disease - Zulfiqar, Irsa; Hussain, Akhtar; Kamran, Areesha; Munir, Khurram; Ajmal Khan, Rida; Rahim Memon, Farzana (Journal of Neonatal Surgery, 2025)
Background:Congenital heart diseases (CHD) remain the most common congenital anomaly worldwide. Maternal diabetes and parental consanguinity have been implicated as significant risk factors. Objective:To determine the association of maternal diabetes mellitus and parental consanguinity with the incidence and pattern of congenital heart disease in Pakistani children. Methods:A cross-sectional study was conducted at the Pediatric Department of Benazir Bhutto Hospital, Rawalpindi over one year (January–December 2024). A total of 300 children aged 0–12 years diagnosed with CHD on echocardiography were enrolled. Data on maternal diabetes, consanguinity, and type of CHD were collected using structured interviews and medical records. Statistical analysis was performed using SPSS v26. Chi-square test was applied; p < 0.05 was considered significant. Results:Out of 300 cases of congenital heart disease (CHD), 174 (58%) were males and 126 (42%) females, with a mean age at diagnosis of 8.6 ± 3.4 months. Maternal diabetes was observed in 54 mothers (18%), significantly higher than the 6% prevalence in the general obstetric population (p < 0.001). Consanguinity was reported in 177 cases (59%). In offspring of diabetic mothers, the most common cardiac lesions were ventricular septal defect (VSD) (33%), transposition of the great arteries (TGA) (22%), and coarctation of the aorta (15%). Among children born to consanguineous parents, atrial septal defect (ASD) (28%), tetralogy of Fallot (TOF) (24%), and patent ductus arteriosus (PDA) (19%) were most frequent. Notably, the combined presence of maternal diabetes and consanguinity was associated with a 3.8-fold increased risk of CHD (odds ratio = 3.8; 95% CI: 2.1–6.5; p < 0.001), highlighting the synergistic effect of these risk factors on congenital cardiac anomalies. Conclusion:Both maternal diabetes and consanguinity significantly increase the risk of congenital heart disease in offspring. Targeted preconception counseling, strict glycemic control, and genetic counseling in consanguineous families are crucial preventive strategies. assessment may aid obstetricians in predicting delivery outcomes and planning labor management..